Nutritional Status and its Determinants in Toddlers: A case study of Hilly region of Uttarakhand - Haldar, Pratiti; Viswanath , Lekha; Srivastava, Ashok Kumar; Sati, Hem Chandra (Indian Journal of Community Health, 2022)
Background: Nutrition in early childhood is of utmost importance specifically for first 1000 days. (1) If in this phase nutrition is neglected, it drags the child into the trap of malnutrition. Aims & Objectives: The objectives were: assess the nutritional status of children and identify the risk factors related to malnutrition in children (1-3) years. Methods & Material: Descriptive exploratory design- conducted in rural villages of Haldwani block, Uttarakhand. Multi stage random sampling technique was used to select 703 children of (1-3) years and their mothers. The children were screened for malnutrition and mothers were interviewed via semi – structured interview schedule. Results: It was found that, 74(11%) children were undernourished, 28 (3.9%) were wasted in mild category and 11 (1.5%) in moderate category. About 87 (12%) were found to be stunted in mild to moderate category. Children below 2.5kg at birth [(1.106, 3.817), p= 0.023], non-initiation of breast feed in one hour [(0.979, 3.344), p=0.055], delayed initiation of weaning [(1.162,4.026), p=0.013] and recurrent illness [(1.187,3.447), p=0.009] were factors associated with malnutrition in children at 95% CI. Conclusion: It is very important to follow up the identified malnourished children so that in the preschool age the nutritional status can be improved.